Risk Management Strategies During COVID-19 in Higher Education: A Case Study - Siddiq, Areesha (Advances in Social Sciences Research Journal, 2022)
The COVID-19 pandemic has significantly impacted Pakistan’s educational sector and has induced higher education institutions (HEIs) to adopt risk management strategies to mitigate the spread of the COVID-19 virus. This study analyzes the risk management strategies employed by Pakistani higher education during COVID-19. The study employed semi-structured interviews, and the qualitative data was collected with objective findings and subjective interviews from 20 respondents working in different academic and administrative positions. This study identifies the challenges the HEIs face to maintain quality education while implementing control measures to maintain health and safety, cope with the shift to online learning, and continuously monitor mitigating measures on campus. In addition, the study provides recommendations based on the challenges perceived by the higher education institutions to implement better risk management strategies, including research-based education, staff training and sensitization, and strict control measures. Lastly, the study provides future directions that suggest analyzing the risk management processes followed by different HEIs around the globe.